2012
DOI: 10.1097/tp.0b013e318245b2af
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of ABO-Incompatible Kidney Transplantation in the United States

Abstract: Background ABO incompatible (ABOi) kidney transplantation is an important modality to facilitate living donor transplant for incompatible pairs. To date, reports of the outcomes from this practice in the United States have been limited to single-center studies. Methods Using the Scientific Registry of Transplant Recipients, we identified 738 patients who underwent live-donor ABOi kidney transplantation between January 1, 1995 and March 31, 2010. These were compared with matched controls that underwent ABO co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
150
2
10

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(175 citation statements)
references
References 47 publications
(39 reference statements)
13
150
2
10
Order By: Relevance
“…The cumulative incidence of graft loss is higher among ABO incompatible recipients (5.9%, 10.4%, 17.4%, and 27.1% at 1, 3, 5, and 10 years) than ABO compatible matched controls (2.9%, 6.4%, 11.0%, and 23.9%) (P = .001). 57 A statistically significant association was seen between higher HLA and ABO compatibility on one hand and immediate graft function on the other…”
Section: Relatedness Human Leukocyte Antigen Matching and Abo Compamentioning
confidence: 82%
“…The cumulative incidence of graft loss is higher among ABO incompatible recipients (5.9%, 10.4%, 17.4%, and 27.1% at 1, 3, 5, and 10 years) than ABO compatible matched controls (2.9%, 6.4%, 11.0%, and 23.9%) (P = .001). 57 A statistically significant association was seen between higher HLA and ABO compatibility on one hand and immediate graft function on the other…”
Section: Relatedness Human Leukocyte Antigen Matching and Abo Compamentioning
confidence: 82%
“…11 In the present study, we used rituximab, double-filtration plasmapheresis, low-dose intravenous immunoglobulin, and immunosuppression with tacrolimus and mycophenolate mofetil. The present results were limited because the long-term outcome of ABO-incompatible kidney transplant is unknown, but we showed that ABO-incompatible kidney transplant can be performed successfully after a preconditioning protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Mūsų tyrimo rezultatai parodė, kad VUL SK Nefrologijos ir inkstų transplantacijos centre jau penktus metus atliekama netapačios kraujo grupės inksto transplantacija efektyvumu nenusileidžia tapačios kraujo grupės inksto transplantacijai iš gyvo donoro. Šios išvados sutampa tiek su kitų šalių pavienių centrų tyrimų rezultatais [11,12], tiek su multicentrinėmis analizėmis [13,14]. Žinoma, mūsų atvejų skaičius nėra didelis.…”
Section: Ab0nunclassified
“…Vis dėlto Montgomery su bendraautoriais [13] apibendrino iki 2010 m. JAV atliktas 738 (1995-2010 m.) AB0n transplantacijas ir palygino jų išeitis su kontroline (AB0s) grupe. Ši multicentrinė analizė parodė, kad atokūs pacientų išgyvenamumo rezultatai tarp grupių statistiškai reikšmingai nesiskyrė (p = 0,2), tačiau transplantatų praradimas statistiškai patikimai didesnis (ypač pirmas dvi savaites po organo persodinimo, p = 0,001) AB0n grupėje.…”
Section: Ab0nunclassified